An Insight into attributes of Stevia rebaudiana Bertoni: Recent advances in extraction techniques, phytochemistry, food applications and health benefits - Sitanshu Khilar; Amrat Pal Singh; Marco Biagi; Alok Sharma (Journal of Agriculture and Food Research, 2022)
Stevia rebaudiana is a sweetener herb belongs to Asteraceae family, native to Argentina, Brazil and Paraguay. Stevia has potential qualities of a sweetener and also constituting a source of many substances with a nutritional effect on the human beings. The leaves of stevia contain stevioside, rebaudioside, steviolbioside, and isosteviol and sweeter than sucrose with zero calories. These steviol glycosides considered for the sweet taste and have commercial value globally as a sugar substitute in foods, beverages and nutraceuticals. The present article provides an overview of different extraction methods, phytochemistry, commercial application of stevia in various products such as confectionary products, bakery, dairy and beverages. Various studies shows promising health benefits of stevia against diverse aliments such as anti-microbial, anti-obesity, anti-cancer, anti-oxidant, anti-hypertensive, anti-diabetic properties considered in the present paper. Clinical studies revealed that steviol glycosides, which are an essential phytochemicals of stevia is safe for human consumption with no acute and subacute toxicity. This study could provides a new direction of stevia for treatment of human diseases and contribute in innovative stevia-based products.